The three pigs - Wiesner, David (New York : Clarion Books, 2001)
The three pigs escape the wolf by going into another world where they meet the cat and the fiddle, the cow that jumped over the moon, and a dragon.
Keywords: Swine -- Fiction; Caldecott Medal; Characters and characteristics in literature -- Fiction